# 17.2: First Order Homogeneous Linear Equations

- Page ID
- 4842

\( \newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} } \)

\( \newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}} \)

A simple, but important and useful, type of separable equation is the *first order homogeneous linear equation*:

Definition: first order homogeneous linear differential equation

A first order homogeneous linear differential equation is one of the form

\[\dot y + p(t)y=0\]

or equivalently

\[\dot y = -p(t)y.\]

"Linear'' in this definition indicates that both \(\dot y\) and \(y\) occur to the first power; "homogeneous'' refers to the zero on the right hand side of the first form of the equation.

Example \(\PageIndex{2}\)

The equation \(\dot y = 2t(25-y)\) can be written \(\dot y + 2ty= 50t\). This is linear, but not homogeneous. The equation \(\dot y=ky\), or \(\dot y-ky=0\) is linear and homogeneous, with a particularly simple \(p(t)=-k\).

Because first order homogeneous linear equations are separable, we can solve them in the usual way:

$$\eqalign{ \dot y &= -p(t)y\cr \int {1\over y}\,dy &= \int -p(t)\,dt\cr \ln|y| &= P(t)+C\cr y&=\pm\,e^{P(t)}\cr y&=Ae^{P(t)},\cr} $$

where \(P(t)\) is an anti-derivative of \(-p(t)\). As in previous examples, if we allow \(A=0\) we get the constant solution \(y=0\).

Example \(\PageIndex{3}\)

Solve the initial value problems \(\dot y + y\cos t =0\), \(y(0)=1/2\) and \(y(2)=1/2\).

**Solution**

We start with

$$P(t)=\int -\cos t\,dt = -\sin t,$$

so the general solution to the differential equation is

$$y=Ae^{-\sin t}.$$

To compute \(A\) we substitute:

$$ {1\over 2} = Ae^{-\sin 0} = A,$$

so the solutions is

$$ y = {1\over 2} e^{-\sin t}.$$

For the second problem,

$$ \eqalign{{1\over 2} &= Ae^{-\sin 2}\cr A &= {1\over 2}e^{\sin 2}\cr}$$

so the solution is

$$ y = {1\over 2}e^{\sin 2}e^{-\sin t}.$$

Example \(\PageIndex{4}\)

Solve the initial value problem \(y\dot y+3y=0\), \(y(1)=2\), assuming \(t>0\).

**Solution**

We write the equation in standard form: \(\dot y+3y/t=0\). Then

$$P(t)=\int -{3\over t}\,dt=-3\ln t$$

and

$$ y=Ae^{-3\ln t}=At^{-3}.$$

Substituting to find \(A\): \(2=A(1)^{-3}=A\), so the solution is \(y=2t^{-3}\).